Micro-sized particle production of Momordica Sp extract using spray dryer - Mel, Maizirwan; Adzhar Yahya, Emirul; Abu Bakar, Mohd Rushdi (IIUM Press, 2011)
Spray drying is the most widely used industrial process involving particle formation and drying. It is highly suited for the continuous production of dry solids in either powder, granulate or agglomerate form from liquid feed-stocks as solutions, emulsions and pump able suspensions. Therefore, spray drying is an ideal process where the end-product must comply with precise quality standards regarding particle size distribution, residual moisture content, bulk density, and particle shape. In this study, Momordica sp extract product has been successfully spray dried into micro scale of powder particle and will be used as plant-based insulin. The process optimized using Taguchi method with four factors and three levels has given a good quality of the product. The average of particle size was obtained at about 11 microns.